On the necessity for biomechanics research in esports - Dupuy, A.; Campbell, M. J.; Harrison, A. J.; Toth, A. J. (Sports Biomechanics, 2024)
This editorial examines the extent to which esports could be considered sports, specifically highlighting the often-neglected biomechanical factors involved in esports. We highlight the dearth of research on the biomechanics required to play competitive video games, drawing attention to topical concerns in traditional sports like performance optimisation, injury prevention, and evidence-based training methods.